Hypercholesterolemia induces T cell expansion in humanized immune mice - (:unkn) unknown (AMER SOC CLINICAL INVESTIGATION INC, 2018)
Emerging data suggest that hypercholesterolemia has stimulatory effects on adaptive immunity and that these effects can promote atherosclerosis and perhaps other inflammatory diseases. However, research in this area has relied primarily on inbred strains of mice whose adaptive immune system can differ substantially from that of humans. Moreover, the genetically induced hypercholesterolemia in these models typically results in plasma cholesterol levels that are much higher than those in most humans. To overcome these obstacles, we studied human immune system-reconstituted mice (hu-mice) rendered hypercholesterolemic by treatment with adeno-associated virus 8-proprotein convertase subtilisin/kexin type 9 (AAV8-PCSK9) and a high-fat/high-cholesterol Western-type diet (WD). These mice had a high percentage of human T cells and moderate hypercholesterolemia. Compared with hu-mice that had lower plasma cholesterol, the PCSK9-WD mice developed a T cell-mediated inflammatory response in the lung and liver. Human CD4+ and CD8+ T cells bearing an effector memory phenotype were significantly elevated in the blood, spleen, and lungs of PCSK9-WD hu-mice, whereas splenic and circulating regulatory T cells were reduced. These data show that moderately high plasma cholesterol can disrupt human T cell homeostasis in vivo. This process may not only exacerbate atherosclerosis, but also contribute to T cell-mediated inflammatory diseases in the hypercholesterolemia setting.
Keywords: SYSTEMIC-LUPUS-ERYTHEMATOSUS; MOUSE MODEL; ATHEROSCLEROSIS; RESPONSES; CHOLESTEROL; METABOLISM; EXPRESSION; REJECTION